Design of a novel 6-DOF haptic master mechanism using MR clutches and gravity compensator. Issue 6 (2nd November 2018) - Song, Byung-Keun; Kang, Seok-Rae; Cha, Seung-Woo; Hwang, Yong-Hoon; Oh, Jong-Seok; Choi, Seung-Bok
Abstract: This work presents design and dynamic analysis results of a novel 6-degrees-of-freedom (6-DOF) haptic master mechanism featured by magneto-rheological (MR) devices and gravity compensator. The design target of the haptic master mechanism is determined on the basis of the possible application to the robotic-assisted minimally invasive surgery (RMIS) system in which a certain magnitude of the force or moment is required to feel by the surgeon. The dynamic torque/force models associated with MR clutches and brakes are derived considering the geometry and Bingham characteristics of MR Fluid. In the mechanism geometry, the wrist part is designed with a symmetrical structure such that the center of gravity is at the center of the handle. This makes the dynamic model of the proposed mechanism to be decoupled between the wrist motion and the translation motion. In addition, a gravity compensator is designed to enhance tracking performances of the desired repulsive forces/torques. It is demonstrated that the proposed 6-DOF MR haptic master can sufficiently generate desired rotational and translational forces/torques required in RMIS system.